O papel do professor coordenador na inserção profissional de professores da educação infantil - Marrega, Aline Cristina da Silva (Universidade Federal de São Carlos, 2022)
This job has a focus on the role of a coordinator teacher into the process of professional insertion of teacher into the education network. The professional insertion of teacher is surrounded by uncertainties and fragilities, the teaching work is very complex and challenging, specially at the beginning of the teaching. The institutional support at the beginning of the carrier may be meaningful for the beginning teacher,that is why the management team has a fundamental role in this process. Therefore, the coordinator teacher should act in a closer way in relation to the beginning teacher`s follow up. From what was exposed, emerge the following question: “What is the role of a coordinator teacher for the period of the professional insertion of the children’s education teacher?” In reference to this study in Huberman (1995, 2000), Garcia (1998, 1999, 2009, 2010), Tardif and Raymond (2000), Cavaco (1992) Tardif (2000), 2004, 2005, 2014), Vaillant and Marcelo (2012), Nóvoa (1995, 2017, 2019, 2022), Franco (2000, 2019), Almeida et al. (2020), Cruz et al (2020), Rinaldi et al. (2022) among others. This research of qualitative nature of descriptive exploratory type, made use of documental analyses, and questionaries with open and close questions as instruments to collect data. The data was organized, analyzed and interpreted through a content analyzes technique, which consisted in making a pre-analyzes through a floating reading, material exploration, dealing with data, inference and interpretation. The data analyzed indicates that the coordinator teachers recognize their responsibility as trainer teachers and reveal a movement to welcome the beginning teachers. These, in turn, legitimize the importance of a coordinator teacher at school, and mention to count on the support with their difficulties. Although, it becomes evident in the answers of the two groups, an inexistence of orientation in relation to the beginning teacher insertion procedures, as education network, due to a variability of actions mentioned in different schools. The research indicates an important contribution to the participating teaching network by pointing out the need for training in order to prepare coordinating teachers for a work aimed at the professional insertion of beginning teachers, such as action can favor the composition of a collective work in educational institutions, what will lead to quality work for early childhood education.
The role of the coordinating teacher in the professional insertion of early childhood education teachers
Keywords: Professor iniciante; Inserção profissional; Coordenador pedagógico; Educação infantil; Beginning teacher; Professional insertion; Pedagogic coordinator; Children’s education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM